Quarantine seed-borne pests of food legumes, cereals, forages and rangelands and their detection methods applied by ICARDA's GHU - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam (International Center for Agricultural Research in the Dry Areas, 2022)
In order to safeguard countries from quarantine risks (insect pests, pathogens, nematodes, parasitic weeds) associated with the movement of germplasm, ICARDA’s Germplasm Health Unit (GHU) follows a regulatory and quarantine program working in close collaboration with competent institutions where ICARDA has platforms for crop breeding, germplasm multiplication and evaluation and genetic resources exchange. ICARDA’s GHU is responsible for the monitoring, clearance and documentation of safe germplasm movement at the center and share the updated technology with the NPPOs in the host countries and farmers. Thus, to confirm the health status of exchanged germplasms, the GHU conducts different types of diagnostic tests based on the nature of the target pest/pathogen. The following is a list of seed-borne pests of food legumes, cereals, forages and rangelands, in addition to their detection methods applied by ICARDA’s GHU (the full procedures of detection methods are available in Kumari et al., 2022a, 2022b):